Literacy, visual culture, and citizenship in education: Information, equity, and learning in a "post truth" era - Linné, Rob; Quinn, Molly (Septentrio Conference Series, 2020)
Brief Abstract: In this presentation, we propose to share, and theorize work in which our education students (in our literacy and curriculum design courses, at Adelphi and Louisiana State universities) explored educational inequities in their local contexts (e.g., differences in school funding in communities on Long Island; in curriculum and pedagogy in schools in Baton Rouge) and created visual representations for communicating the knowledge gained and contemplating how to create alternatives that might work in ways aimed at promoting greater justice. Critical readings of and compelling representations for communicating knowledge, and access to such via education, are particularly called for in the present historical moment wherein equity is increasingly at issue, and access to information while abundant arrives also exponentially and overwhelmingly within an excess of misinformation. Full Proposal: Critical readings of and compelling representations for communicating knowledge, and access to such via education, are particularly called for in the present historical moment wherein equity is increasingly at issue, and access to information while abundant arrives also exponentially and overwhelmingly, part and parcel with an excess of misinformation. Scarcely, then, has there been a time when literacy writ large—involving multiple media and digitized platforms in a highly and progressively growing visual culture is requisite to enlightened and engaged citizenship (Kinloch, 2010). In an era at once described as post-truth (Keyes, 2004) and post-racial (Shorr, 2008; Wootens, 1971), and yet marked, in our US context—albeit with global contours, by such policies and practices as “the New Jim Crow” (Alexander, 2012) and “school to prison pipeline” (Fasching-Varner, Mitchell, Martin and Bennett-Haron, 2014; Heitzeg, 2016; Okilwa, Khalifa and Briscoe, 2017), disproportionately acting upon, criminalizing and incarcerating African-Americans—amid the growth as well of renewed forms of nationalism, racism, re-segregation and educational disparity (Bell, 2004; Dixson and Rousseau, 2004; Logan and Burdick-Will, 2017; Love, 2019; McFarland and Hussar, 2019; Norwicki, 2018), that also fall upon economic lines particularly detrimental to opportunities and outcomes not only for people of color but also for all those who are low-income or in poverty (Gorski, 2017); as educators and scholars we were particularly interested in working with students in ways that might induce us to critically recognize, read, reckon with, and creatively respond to such realities. In this presentation, and paper, we propose to share, and theorize concerning, something of the fruits of such work in which our education students (in our teaching literacy and curriculum design courses, at Adelphi and Louisiana State universities) explored educational inequities in their local contexts (e.g., differences in school funding in communities on Long Island; in curriculum and pedagogy in schools in Baton Rouge) and created visual representations for communicating the knowledge gained and contemplating how to create alternatives (Pirbhai-Illich, Pete & Martin, 2017; Seidel & Jardine, 2014; Snaza, Sonu, Truman, & Zaliwska, 2016) that might work in ways aimed at promoting greater justice.